Judiska inslag i det kristna Etiopien - Witakowski, Witold (Nordisk judaistik, 1996)
Ethiopian Christianity has often been regarded by European travelers and missionaries as impure, because of the presence in it of what were believed to be Jewish customs and ideas. The Ethiopians regard themselves as "The Children of Israel". This tradition seems to be based on legend contained in the national epos "The Glory of the Kings" (14th cent.), according to which the founder of the Ethiopian imperial dynasty, of which Haile Sellassie was the last scion, was Menilek, the son of the King Solomon and the Queen of Sheba. The Ethiopian customs for which Jewish origins can be presumed include circumcision, the prohibition of eating meat from pigs and some other animals, in accordance with Leviticus 11. Moreover, until recently there were living in Ethiopia (but are now in Israel) Falashas, who profess an unusual form of Judaism. They do not know the Talmud whereas most of their religious literature, written in Ge’ez, is borrowed from their Christian neighbours. The usual architectural plan of Ethiopian church buildings follows that of the Temple in Jerusalem and the Tabernacle. Three theories have been propounded so far to explain the origin of the Jewish elements in Ethiopian Christianity, and also the origin of the Falashas.